Recruitment and Selection in Canada, 6th ed. - Maillet, Stéphanie (Relations industrielles / Industrial Relations, 2017)
Thiis article reviews the book, "Recruitment and Selection in Canada," by Victor M. Catano, Willi H. Wiesner, and Rick D. Hackett.